Is oestrogen an important player in melanoma progression? - Janik, Marcelina E.; Bełkot, Klaudyna; Przybyło, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2014)
The oestrogen-dependent regulation of cell behaviour is realised by stimulation of specific oestrogen receptors. The classical oestrogen receptors ERαand ERβ are transcription factors, and they modulate expression of hormonally regulated genes, while the third one, GPER, is thought to be responsible for the observed rapid, non-genomic cellular response. Oestrogen dependency is attributed to a number of cancers, including breast, ovarian and endometrial cancer; however, there is still growing evidence that melanoma should also be cited as a hormonally dependent tumour. This comes from the observations of gender-related differences in melanoma progression and reports concerning the history of the malignant course of melanomas during pregnancy. Although, the observations of oestrogen regulation of melanoma progression are controversial, the effect of oestrogen should not be neglected, as the skin possesses its own hormonal microenvironment. This aspect of melanoma progression should be taken under careful consideration as it may offer new therapeutic possibilities.